Update on Diagnostics for DLR's Electric Propulsion Test Facility. (2017) - Neumann, Andreas
Abstract: DLR has operated since the end of 2011 a dedicated electric propulsion (EP) test facility, the High Vacuum Plume Test Facility Göttingen – Electric Thrusters (STG-ET). This EP test facility has now accumulated several years of thruster testing experience. Special features characterize this facility tailored to electric space propulsion testing. In the first place, a large vacuum chamber mounted on a low vibration foundation characterizes the facility. A performant pumping system ensures a good vacuum, and a target with low sputtering coating dumps the beam power. The vacuum chamber is 12m long and has a diameter of 5m. With respect to thruster tests, the design focus is on accurate thrust measurement, plume diagnostics, and plume interaction with spacecraft components. Electric propulsion thrusters have to run for thousands of hours, and with this the facility is prepared for long-term experiments. The present paper gives an overview of the facility, and describes the vacuum chamber, pumping system, diagnostics, and experiences with these components. After commissioning of STG-ET, the main focus was put on the testing of Hall-effect and gridded ion thrusters.